On the interaction between modal and aspectual periphrases - Laca, Brenda (Borealis – An International Journal of Hispanic Linguistics, 2019)
This paper explores the semantics of combinations in which a modal verb is preceded by a progressive, an incremental or a habitual periphrasis. Two distinct readings in context, aspectualized VP and aspectualized modality readings, are found to correlate with the (not-)at- issue status of the modal according to Tonhauser's diagnostics. Implicative readings (a generalization of the more restrictive notion of actuality entailments) emerge obligatorily in aspectualized VP readings, but are also present in some aspectualized modality readings. Aspectualized modality readings provide evidence for the claim that modalized event descriptions are stative.